A identidade profissional dos professores formadores nos cursos de licenciatura em matemática - CUNHA NETO, Júlio Henrique da (2016)
The study is part of the concerning issue of the higher education teacher’s formation, in particular, the formation teacher of Bachelor’s Degree in Mathematics courses. Thus, the guiding question in this research was: How do formation teachers of Bachelor’s Degree in Mathematics coursescreate their professional identity? We aimed, therefore, to understand how the professional identity of formationteachers in Bachelor’s Degree in Mathematics coursesis created. The theoretical frameworkis based, at first, on studies about the higher education, the formation teacher and the Bachelor's Degree in Mathematics, in which we sought to understand the scenario in which the teachers are inserted, as well as their duties and work conditions. Later, the identity and the teacher’s professional identity were addressed, also including the socialization processes. Through a qualitative approach, semi-structured interviews with five teachers of a Bachelor’s Degree in Mathematics course from a public university in the Triangulo Mineiro (MG) were carried out and the data were analyzed by means of prose analysis. The results reveal that formation teachers have been developing their identity by means of socialization processes, being primary and secondary socialization consisted of family attributes, school, graduation and post-graduation, the professional field and mathematical knowledge, a process that happens in the dialectic between these teachers and society. The uncertainty of habitus in this process, either as structuring of an identityor as challenging for a new identity, and this duality in the process of an individual’s identitycreation, with objective and subjective elements, haveengendered a professional identity in formation teachers which is marked by such socialization processes and by the experiences that have been revealed in the practice of these teachers.